(untitled) (Inženierzinātņu un augstskolu vēsture, 2020)
Rakstā apkopots Rīgas Politehniskā institūta (RPI) Celtniecības fakultātes absolventa (1968) Andra Staģa veikums inženiera profesijā, kā arī atklāts viņa devums Latvijas sporta vēsturē un statistikā, sasniegumi vieglatlētikā un to popularizēšana. Tas ir pirmais pētījums par inženiera, Triju Zvaigžņu ordeņa virsnieka, Latvijas čempiona vieglatlētikā un sporta vēstures grāmatu autora, žurnālista A. Staģa darbību un dzīvi. Pētījuma mērķis ir atklāt A. Staģa devumu un viņa personības nozīmi Latvijai, izmantojot viņa un autoru personīgos arhīvus, Latvijas Valsts arhīva dokumentus, Latvijas Nacionālās bibliotēkas krājumu.The article summarizes the achievements of Andris Staģis, a graduate of the Faculty of Civil Engineering of Riga Polytechnic Institute (RPI; 1968), in the profession of an engineer, as well as reveals his contribution to the history and statistics of Latvian sports, achievements in athletics and their promotion. This is the first study on the activities and life of engineer, officer of the Order of the Three Stars, Latvian champion in athletics and the author of sports history books, and journalist A. Staģis. The aim of the research is to reveal the contribution of A. Staģis and the significance of his personality to Latvia using his and the authors’ personal archives, documents of the State Archives of Latvia, and the collection of the National Library of Latvia.